A Framework for Quality Assurance of Pediatric Revisits to the Emergency Department. Issue 12 (December 2021) - Marchese, Ronald F.; Taylor, April; Voorhis, Catherine B.; Wall, Jessica; Szydlowski, Ellen G.; Shaw, Kathy N.
Abstract : Background: Emergency department return visits significantly impact medical costs and patient flow. A comprehensive approach to understanding these patients is required to identify deficits in care, system level inefficiencies, and improve diagnosis specific management protocols. We aimed to identify factors needed to successfully analyze return visits to explore root causes leading to unplanned returns and inform system-level improvements. Methods: A multidisciplinary committee collaborated to develop a quality review process for return visits within 72 hours to our pediatric emergency department that were then subsequently admitted to the hospital. The committee developed methodology and a web-based tool for chart review and analysis. Results: Of 197, 076 ED visits (159, 164 discharged at initial visit), 5390 (3.4%) patients were discharged and represented to the ED within 72 hours and 1658 (1.0%) of those resulted in admission. Using defined criteria, approximately one third (n = 564) of revisits with admission were identified for chart review. Reason for revisit included natural progression of disease (67.6%), new condition or problem (11.2%), diagnostic error (6.9%), and scheduled or planned readmissions (3.5%). All diagnostic errors had not been previously identified by ED leadership. Of the reviewed cases, most were not preventable (84.0%); however, a number of system-level actions resulted from discussion of the potentially preventable revisits. Conclusions: Seventy-two-hour ED revisits were efficiently and systematically categorized with determination of root causes and preventability. This process resulted in shared provider-level feedback, identifying trends in revisits, and implementation of system-level actions, therefore, encouraging other institutions to adopt a similar process.